Transcriptomic Analysis of Genes Involved in Plant Defense Response to the Cucumber Green Mottle Mosaic Virus Infection - Anna Slavokhotova; Tatyana Korostyleva; Andrey Shelenkov; Vitalii Pukhalskiy; Irina Korottseva; Marina Slezina; Ekaterina Istomina; Tatyana Odintsova (Life, 2021)
Plants have evolved a complex multilayered defense system to counteract various invading pathogens during their life cycle. In addition to silencing, considered to be a major molecular defense response against viruses, different signaling pathways activated by phytohormones trigger the expression of secondary metabolites and proteins preventing virus entry and propagation. In this study, we explored the response of cucumber plants to one of the global pathogens, cucumber green mottle mosaic virus (CGMMV), which causes severe symptoms on leaves and fruits. The inbred line of Cucumis sativus L., which is highly susceptible to CGMMV, was chosen for inoculation. Transcriptomes of infected plants at the early and late stages of infection were analyzed in comparison with the corresponding transcriptomes of healthy plants using RNA-seq. The changes in the signaling pathways of ethylene and salicylic and jasmonic acids, as well as the differences in silencing response and expression of pathogenesis-related proteins and transcription factors, were revealed. The results show that silencing was strongly suppressed in infected plants, while the salicylic acid and ethylene signaling pathways were induced. The genes encoding pathogenesis-related proteins and the genes involved in the jasmonic acid pathway changed their expression insignificantly. It was also found that WRKY and NAC were the most sensitive to CGMMV infection among the transcription factors detected.